Effect of Marketing Mix and Electronic Word of Mouth (E-Wom) on Purchase Decisions on Olenka Coffee and Dining in Banda Aceh - Dhandi Muslizar; Trisha Gilang Saraswati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Banda Aceh is known as the land of a thousand coffee shops . Olenka Coffee and Dining is a contemporary coffee shop that has a minimalist theme that is in great demand by young people in Banda Aceh. At the beginning of its opening, Olenka Coffee and Dining posted good sales, but over time the Covid-19 pandemic sales decreased. Olenka Coffee and Dining  realizes that during this pandemic, effective promotions use the marketing mix and electronic word of mouth because the reviews from consumers have quite affected sales at Olenka Coffee and Dining. The marketing mix applied at Olenka encountered several problems related to promotion, price & place, which could reduce sales at Olenka. Electronic word of mouth at Olenka Coffee and Dining  is quite influential on sales because consumers sometimes directly give negative reviews through digital platforms without first complaining to Olenka Coffee and Dining.  The purpose of this study was to determine the influence of marketing mix and electronic word of mouth on purchasing decisions at Olenka Coffee and Dining. This study uses quantitative methods of descriptive research with multiple linear regression analysis techniques.sampling technique used was non-probability sampling, the type of accidental sampling with the number of samples used as many as 100 respondents who were Olenka Coffee and Dining  who had bought directly at Olenka Coffee and Dining.Coffeetest was carried out using SPSS version 25. Based on the results of the descriptive analysis in this study, the marketing mix at Olenka and Dining included in the good category with an average percentage of 77%. Electronic word of mouth at Olenka Coffee and Dining in the good category with a percentage of 74%, and the purchase decision of Olenka Coffee and Dining is in the good category with a percentage of 77%. Therefore, with the results that researchers get, it is hoped that Olenka Coffee and Dining will further improve its marketing mix and also further increase interaction with consumers through Instagram, because with this interaction it can increase Olenka insights Coffee and Dining